Zircon U-Pb geochronology of the Lan Sang gneisses and its tectonic implications for the Mae Ping shear zone, NW Thailand - Lin, Yu-Ling; Lee, Tung-Yi; Lee, Hao-Yang; Iizuka, Yoshiyuki; Quek, Long Xiang; Charusiri, Punya (Frontiers in Earth Science, 2023)
The Mae Ping shear zone (MPSZ), a major shear zone trending NW-SE in Thailand, is responsible for the left-lateral displacement of the N-S Triassic-Jurassic granitoid and gneiss belt. This displacement is postulated to have contributed to Cenozoic extrusion tectonics. Within the Lan Sang National Park, the MPSZ exposes several intensely deformed lithologies, collectively known as the Lan Sang gneisses. These gneisses have attracted considerable attention for their potential to substantiate the extrusion model. However, the timing of the emplacement of the orthogneiss protolith is still debated. Moreover, the origin and distribution of the Eocene syn-shearing granodiorite within this shear zone are not well understood. To shed light on the magmatic history of the MPSZ, this study utilized zircon U-Pb geochronology to systematically investigate the Lan Sang gneisses. Our findings demonstrate that these gneisses can be categorized into paragneiss and orthogneiss groups. Paragneiss samples feature zircons displaying rounded detrital cores ranging from 3,078 to 450 Ma, with metamorphic rim overgrowth of ca. 200 Ma (most Th/U <0.01). This indicates that their Paleozoic sedimentary protoliths experienced high-grade metamorphism during the Triassic-Jurassic Indosinian orogeny. On the other hand, zircon from orthogneiss samples shows that their magmatic protoliths were predominantly emplaced either around ∼200 Ma or within 45-32 Ma. The Eocene-Oligocene magmatism likely coincided with the proposed Eocene metamorphism. Since these samples were deformed by left-lateral shearing, the left-lateral motion of the MPSZ probably ended after 32 Ma. Eocene-Oligocene magmatic events have also been identified in granite, mylonite, and gneiss samples from other regions along the Sibumasu terrane, including the Three Pagodas, Klaeng, Ranong, Khlong Marui shear zones, and the Doi Inthanon area. The Eocene-Oligocene magmatism was likely linked with the movement of the shear zones and may be responsible for the regional cooling pattern. The spatial and temporal distribution of the Eocene-Oligocene magmatism within the Sibumasu terrane supports the hypothesis that the inward migration of magmatism in the overriding plate resulted from the shallowing of the Neo-Tethyan slab.